Recent Advances in Indocyanine Green-Based Probes for Second Near-Infrared Fluorescence Imaging and Therapy - Dehong Hu; Menglei Zha; Hairong Zheng; Duyang Gao; Zonghai Sheng (Research)
Fluorescence imaging, a highly sensitive molecular imaging modality, is being increasingly integrated into clinical practice. Imaging within the second near-infrared biological window (NIR-II; 1,000 to 1,700 nm), also referred to as shortwave infrared, has received substantial attention because of its markedly reduced autofluorescence, deeper tissue penetration, and enhanced spatiotemporal resolution as compared to traditional near-infrared (NIR) imaging. Indocyanine green (ICG), a US Food and Drug Administration-approved NIR fluorophore, has long been used in clinical applications, including blood vessel angiography, vascular perfusion monitoring, and tumor detection. Recent advancements in NIR-II imaging technology have revitalized interest in ICG, revealing its extended tail fluorescence beyond 1,000 nm and reaffirming its potential as a clinically translatable NIR-II fluorophore for in vivo imaging and theranostic applications for diagnosing various diseases. This review emphasizes the notable advances in the use of ICG and its derivatives for NIR-II imaging and image-guided therapy from both fundamental and clinical perspectives. We also provide a concise conclusion and discuss the challenges and future opportunities with NIR-II imaging using clinically approved fluorophores.